Characterization of the novel HLA‐A*03:436 allele by sequencing‐based typing. (9th February 2022) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Wojciechowski, Elodie; Visentin, Jonathan
Abstract : HLA‐A*03:436 differs from HLA‐A*03:01:01:05 by one nucleotide substitution in codon 26 in exon 2.